Sustainable use of traditional geomaterials in construction practice - Přikryl, Richard; Török, Ákos, 1963-; Gómez-Heras, M.; Miskovsky, K.; Theodoridou, M. (The Geological Society, 2016)
Geomaterials derived from the Earth's crust and used in construction after appropriate processing are among the earliest raw materials exploited, processed and used by humans. Their numerous functional properties include accessibility, workability and serviceability, and these are explored within this volume. In modern society, sustainable use of raw materials, specifically those exploited in large volumes such as geomaterials for construction, raises questions of reducing extraction of primary resources and thus minimizing impacts on natural systems, and also employment of materials and technologies to lower emissions of deleterious substances into the atmosphere. This will be possible only if we fully understand the properties, processing and mode of use of traditional geomaterials. Although most of the papers within this volume were written by geologists, the contributions will also be of interest to those working in cultural heritage, monument conservation, civil engineering and architecture.
Keywords: Building materials.; Raw materials.; Sustainable construction.; elektronické knihy; electronic books